2011
DOI: 10.1039/c1ee01437d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped carbon xerogel: A novel carbon-based electrocatalyst for oxygen reduction reaction in proton exchange membrane (PEM) fuel cells

Abstract: A low-cost, novel carbon-based electrocatalyst for oxygen reduction reaction (ORR), nitrogen-doped carbon xerogel (N-CX) was synthesized via a sol-gel polymerization method followed by a pyrolysis process. The N-CX catalyst exhibited a high activity for ORR, and a good stability in acid media. A high performance with a maximum power density of 360 mW cm À2 was achieved on a single PEM fuel cell with N-CX as the cathode electrocatalyst.As one of the key materials of PEM fuel cells, the electrocatalyst for oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 56 publications
6
119
0
1
Order By: Relevance
“…Among various carbon materials, carbon aerogels are of particular interest given that they can be easily synthesized towards uniform, low density lightweight and controllable structures M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 (i.e. monolith, bead, powder or thin film) with excellent mass transfer properties, low thermal conductivity and dielectric permittivity [2,3]. Structural features such as micro-, meso-and macro-porosity, arrangement of carbon network and surface functionality are controlled by the employed drying technique (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Among various carbon materials, carbon aerogels are of particular interest given that they can be easily synthesized towards uniform, low density lightweight and controllable structures M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 (i.e. monolith, bead, powder or thin film) with excellent mass transfer properties, low thermal conductivity and dielectric permittivity [2,3]. Structural features such as micro-, meso-and macro-porosity, arrangement of carbon network and surface functionality are controlled by the employed drying technique (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2b, it can be observed that the Co-NCX-20 presents an amorphous microstructure, not graphitic structure, due to the low pyrolysis temperature and the original 3D-net structure for RF resin. According to our previous work [39], this unique structure is expected to expose more planar edges and defective due to N-doping, which is supposed to offer more reactive sites for ORR [44]. Fig.…”
Section: 2mentioning
confidence: 99%
“…The NCX catalysts were prepared according to our previous work [39]. Briefly, 6.16 g resorcinol (R) was dissolved in 7 ml deionized water and mixed with 8.4 ml formaldehyde (F) solution (37% formaldehyde, aq.).…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] The carbon catalyst does not suffer activity degradation caused by Pt nanoparticles agglomeration and loss as Pt/C does, which maybe also contributes to their high stability. [37,38] The formation of graphitic carbon may also play a significant role in the improvement of the corrosion resistance for the carbon-based catalyst. [17] In summary, we have developed a facile approach for the synthesis of nitrogen-doped carbon electrocatalysts with polyaniline as carbon source by a polymerization process combined with further pyrolysis under an ammonia atmosphere.…”
Section: à2mentioning
confidence: 99%